The influence of surface parameters of coatings deposited by various vacuum-plasma methods on the cell/material interaction in vitro tests - Zykova, A.; Safonov, V.; Luk’yanchenko, V.; Walkowicz, J.; Rogowska, R. (Вопросы атомной науки и техники, 2007)
The surface of an implant plays a basic role in determining biocompatibility and integration due to its direct contact with the adjacent tissues. There is now the good understanding that life time of orthopedic implants and the design of the novel tissue-engineering medical products may be associated with local and remote biological tissue response and cell-material interaction. Material properties such as implant surface composition, roughness, topography can influence events at bone –implant interfaces and cell response to implant material.